You know b=-6 and since you know this, you can plug -6 in for b.
This would become 4(-6) + 6 divided by 6.
You can then multiply 4 and -6 together,
-24 + 6 / 6
You can then add -24 and 6 together,
-18/6
You can then divide -18 by 6,
-18/6=-3
-3 is your final answer
Answer:
-6.3
Step-by-step explanation:
7/10 X -9/1 = -63/10 = -6.3
I would say the answer is 2
Answer:
(2, -3)
Step-by-step explanation:
Apparently, the equations are supposed to be ...
The solution for x can be found by subtracting the second equation from the first:
(4x +y) -(3x +y) = (5) -(3)
x = 2 . . . . . . . matches the second answer choice
Y can be found from either equation:
y = 5 - 4x . . . . . subtract 4x from the first equation
y = 5 -4(2) = -3
The solution is (x, y) = (2, -3).